Penerapan Pendekatan Computational Thinking terhadap Kemampuan Pondasi pada Materi Energi Dan Perubahannya Kelas 3 SD Negeri Bhaktikarya - Esti Nur Indah Sari; Elizabeth Daniar Ratih Nursanti; Muhammad Fadholi; Christiyanti Aprinastuti; Yuliana Rismiyati (Universitas Muhammadiyah Magelang, 2023)
Computational Thinking is included as a learning approach that can identify patterns, solve complex problems into simpler steps, organize and create a series of steps in providing solutions. This study aims to analyze the ability of students' foundations of abstraction, pattern recognition, and algorithms through the application of the Computational Thinking approach. The research method used is descriptive research with a case study type. This study uses quantitative and qualitative data analysis techniques. The subjects of this study were 24 third grade students who were divided into 12 small groups at Bhaktikarya Public Elementary School. The results of this study indicate that the application of the Computational Thinking approach to the results of Student Worksheets that apply students' abstraction foundation skills, pattern recognition, and algorithms through the application of the Computational Thinking approach obtained an average percentage of 66%. This percentage is in the sufficient category.